The importance of ethics in the role of arbitrators - Collazos Ortiz, Adriana (Revista Análisis Internacional (Cesada a partir de 2015), 2013)
La importancia de la ética en el papel de los árbitros, es un documento de investigación que analiza varios casos de arbitraje internacional, desde los que se estudia el valor de la neutralidad y de los deberes de los árbitros cuando son partícipes en un conflicto. International Arbitration has become the most effective process to resolve commercial disputes between international actors. Arbitration is attractive for business players because it (i) creates predictability in the international commercial world; (ii) prevents parallel litigation in different countries and, (iii) assures neutrality in the dispute resolution. However, if the arbitrators are not ethical “judges”, these benefits will not exist. The importance of arbitrators’ ethics has been recognized by international authorities for decades. Recently, two important codified guidelines for arbitrators’ ethics have been modified. The American Arbitration Association’s Code of Ethics for Arbitrators in Commercial Disputes and the International Bar Association’s Guidelines on Conflicts of Interest in International Arbitration reformed the old Triple A’s Code and IBA Rules respectively. This paper intends to compare and contrast the ethical rules that have been modified with the new guidelines issued by the organizations mentioned above. The objectives are to explain the development of the ethical rules for arbitrators’ behavior and to discuss the scope of the duty of disclosure, material facts to be disclosed, conflicts of interest, and the neutrality of the party nominee arbitrator. Commonwealth Coatings v. Continental Casualty, AT & T Corp. v. Saudi Cable Company, Merit Insurance v. Leatherby Insurance and Sunkist v. Sunkist will be the cases discussed as the judicial context of the ethical rules.